2013
DOI: 10.1016/j.orggeochem.2012.12.009
|View full text |Cite
|
Sign up to set email alerts
|

Identification and quantification of polyfunctionalized hopanoids by high temperature gas chromatography–mass spectrometry

Abstract: Hopanoids are triterpenoids produced mainly by bacteria, are ubiquitous in the environment, and have many important applications as biological markers. A wide variety of related hopanoid structures exists, many of which are polyfunctionalized. These modifications render the hopanoids too involatile for conventional gas chromatography (GC) separation, so require either laborious oxidative cleavage of the functional groups or specialized high temperature (HT) columns. Here we describe the systematic evaluation a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
56
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 58 publications
(57 citation statements)
references
References 48 publications
0
56
0
1
Order By: Relevance
“…However, within this Py‐compound class, the sterol forms are a useful proxy for OM degradation status because of the high susceptibility to degradation [ Mackenzie et al , ]. Hopanoids are known to derive from the cell membranes of prokaryotes, especially bacteria [ Meredith et al , ; Sessions et al , ], but have not been determined directly with Py‐GC/MS and are rarely reported [ Buurman et al , ]. Similarly, the tocopherols are abundant in most photosynthetic organisms, because of their fundamental role in the photosynthetic process [ Maeda and DellaPenna , ].…”
Section: Resultsmentioning
confidence: 99%
“…However, within this Py‐compound class, the sterol forms are a useful proxy for OM degradation status because of the high susceptibility to degradation [ Mackenzie et al , ]. Hopanoids are known to derive from the cell membranes of prokaryotes, especially bacteria [ Meredith et al , ; Sessions et al , ], but have not been determined directly with Py‐GC/MS and are rarely reported [ Buurman et al , ]. Similarly, the tocopherols are abundant in most photosynthetic organisms, because of their fundamental role in the photosynthetic process [ Maeda and DellaPenna , ].…”
Section: Resultsmentioning
confidence: 99%
“…C-30 hopanoids, methylsterols, and tetrahymanol were analyzed via hightemperature gas chromatography-mass spectrometry (GC-MS) (52). Tetrahymanol was quantified by comparison with a cholestanol standard added to samples before derivatization and was normalized to the largest hopene peak detected in the sample.…”
Section: Construction Of Tetrahymanol Synthase Mutantsmentioning
confidence: 99%
“…The GC was coupled to a 5977A Series MSD with the source at 230°C and operated at 70 eV in EI mode scanning from 50 to 850 Da in 0.5 s. Aminohopanoids were detected via liquid chromatography-mass spectrometry at the Vincent Coates Foundation Mass Spectrometry Laboratory, Stanford University (mass-spec.stanford.edu). All lipids were identified based on their retention time and comparison with previously published spectra (33,52,53).…”
Section: Construction Of Tetrahymanol Synthase Mutantsmentioning
confidence: 99%
“…These samples appear in Figure 2 with either an identifier, if hopanoids were analyzed, or blank, if hopanoids were not analyzed. We also attempted to quantify hopanoids, specifically unextended hopanoids that cannot be identified by liquid chromatography-mass spectrometry, using standard GC-MS techniques (Sessions et al, 2013), but we were unable to unambiguously detect hopanoids due to a high background. Samples Figure S2).…”
Section: Hpnp Correlation With Plantsmentioning
confidence: 99%
“…were extracted as previously reported (Sessions et al, 2013). Methylated and non-methylated bacteriohopanepolyols were identified by liquid chromatographymass spectrometry as previously described (Welander et al, 2012).…”
Section: Hpnp Correlation With Plantsmentioning
confidence: 99%